Brazilian Polycladida (Rhabditophora: Platyhelminthes): Rediscovery of Marcus’ type material and general revision - Bahia, Juliana; Schrödl, Michael (Zootaxa, 2018)
Polyclads are a conspicuous group of marine invertebrates, the most charismatic members of the phylum Platyhelminthes. From Brazil, a total of 71 polyclad species were reported or described. Only three of them were recently described, five are recent records for the Brazilian coast, and 55 were described by Ernest and Eveline Marcus, who were by far the most productive workers. However, they quite often published in Portuguese or German, rather than English, and have not designated type material or specified material deposited in museum collections. Most of the polylcad material studied by the Marcus was found to be in the Swedish Museum of Natural History. Here we summarize the knowledge about Brazilian polyclad biodiversity, give information about deposited material in different museums for future reference, and designate type material for the species that did not have any. We examined 58 polyclad species reported from Brazil and designated type material and information available on type series of 52 species. Lectotypes (89 vouchers) were designated for 30 species and paralectotypes (73 specimens / 70 vouchers) were designated for 22 Brazilian species. Among the 261 type vouchers examined in this work, 22 species (77 vouchers) had material recognized as holotypes and 2 vouchers were recognized as paratypes. Of the total number of species reported from Brazil, 10 species remain without information about type material. In the present paper we also propose a new combination (Lurymare cynarium nov. comb.). Eleven species have their geographical distribution range broadened and 42 were photographed for the first time, five of those were photographed live as well. The number of Brazilian polyclad species is expected to rise when different regions and environments are surveyed.